2002
DOI: 10.1007/s00705-002-0848-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence of the Pepino mosaic virus RNA genome

Abstract: Analysis of an RNA-seq strand-specific library revealed a complete ge-nome of Hardenbergia mosaic virus (HarMV) from RNA extracted from a native wiste-ria (Hardenbergia comptoniana) plant from southwest Australia. We compared it with eight other complete HarMV genomes. It most resembled (85.8% nucleotide identity) the genome of HarMV isolate MD4-D. I n July 2016, an apical leaf sample showing obvious mosaic and deformation symptoms was collected from a plant of the indigenous southwest Australian species nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0
9

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 10 publications
1
85
0
9
Order By: Relevance
“…Damage and economic losses caused by PepMV vary greatly and can at least partially be attributed to the differential symptomatology caused by different PepMV isolates (Hanssen et al, 2009(Hanssen et al, , 2010a. Currently, four PepMV genotypes are distinguished: the Peruvian genotype (LP), which was first isolated from Solanum peruvianum and is similar to the original pepino (S. muricatum) isolate (Ló pez et al, 2005;Pagán et al, 2006); the European tomato genotype (EU), which was first reported in greenhouse tomato production in Europe (Mumford and Metcalfe, 2001;Aguilar et al, 2002;Cotillon et al, 2002;Verhoeven et al, 2003;Pagán et al, 2006); the CH2 genotype, which was first isolated from tomato seeds from Chile (Ling, 2007); and the US1 genotype, which was first described in the United States (Maroon-Lango et al, 2005). In recent years, the CH2 genotype has largely replaced the EU genotype in commercial tomato production in several European countries (Hanssen et al, 2008;Gó mez et al, 2009).…”
mentioning
confidence: 99%
“…Damage and economic losses caused by PepMV vary greatly and can at least partially be attributed to the differential symptomatology caused by different PepMV isolates (Hanssen et al, 2009(Hanssen et al, , 2010a. Currently, four PepMV genotypes are distinguished: the Peruvian genotype (LP), which was first isolated from Solanum peruvianum and is similar to the original pepino (S. muricatum) isolate (Ló pez et al, 2005;Pagán et al, 2006); the European tomato genotype (EU), which was first reported in greenhouse tomato production in Europe (Mumford and Metcalfe, 2001;Aguilar et al, 2002;Cotillon et al, 2002;Verhoeven et al, 2003;Pagán et al, 2006); the CH2 genotype, which was first isolated from tomato seeds from Chile (Ling, 2007); and the US1 genotype, which was first described in the United States (Maroon-Lango et al, 2005). In recent years, the CH2 genotype has largely replaced the EU genotype in commercial tomato production in several European countries (Hanssen et al, 2008;Gó mez et al, 2009).…”
mentioning
confidence: 99%
“…En el gen del TGBp1 se observa un (región intergénica entre el TGB y la ORF5), se encuentra la última región del genoma del virus, que codifica para la proteína de la cápside (CP) de 25 kDa, y en la cual se encuentra la secuencia conservada de naturaleza antifática 5´KFAAFDFFDGVT 3´, responsable posiblemente de la unión del RNA viral a la CP mediante interacciones hidrofóbicas. En su extremo 3´, tras una serie de nucleótidos que no se traducen (3´UTR), se encuentra la cola poli-A (Aguilar et al, 2002;Cotillon et al, 2002;Maroon-Lango et al, 2005;Ling, 2007;Hasiów et al, 2007).…”
Section: Estructura De La Partícula Viral Y Organización Genómicaunclassified
“…(Jordá et al, 2001b;Córdoba et al, 2004a) y una planta aromática (Ocimum basilicum L.) procedente de invernaderos de Silicia (Davino et al, 2009 Asimismo, en diversos estudios efectuados se han determinado experimentalmente una serie de especies hospedantes artificiales del virus, todas pertenecientes a la familia Solanaceae (Tabla 1.5), así como una serie de plantas habitualmente empleadas como plantas indicadoras que han resultado siempre no hospedantes (Tabla 1.6). Cabe destacar que existen dos especies, Chenopodium murale L. (Jones et al, 1980;Aguilar et al, 2002) y O. basilicum (Salomone y Roggero, 2002;Davino et al, 2009) Jordá et al, 2001a;Salomone y Rogero, 2002;Verhoeven et al, 2003 Nicotiana affinis T.Moore Solanaceae Pospieszny et al, 2008 N. benthamiana Domin. Solanaceae Jordá et al, 2001a;Aguilar et al, 2002;Salomone y Roggero, 2002;Davino et al, 2008;Pospieszny et al, 2008 N. bigelovii (Torr.)…”
Section: Transmisiónunclassified
See 2 more Smart Citations